Employee And Decision-Maker Perceptions On Job Related And Personal Characteristics Suited For Teleworking: A Study In The Malaysian Telecommunication Industry - Aswawi, Arnifa (2002)
There is a vast amount of literature addressing the remarkable growth of teleworking in the western societies. The literature covers various topics such as people's perception towards teleworking, the impact of teleworking on individuals and traits of successful teleworkers. There are also legal and human resource issues surrounding the implementation of teleworking. In Malaysia, this new work style has yet to penetrate the business environment. Reported research on this topic is still very limited, confined mostly to perceptual and prevalence studies. This study intended to broaden the horizon by focusing on the individual and job-related aspects of teleworking. The sample of the study comprised of employees from four functional departments in a local telecommunication company. The objective was to discover job functions that can be teleworked. In addition , the study wanted to look into the differences and similarities in the personalities of the employees from these departments. As the company had never practised teleworking, it was also deemed necessary to investigate the perception of employees towards this alternative work mode. The main conclusion from this study is that the perception of all the respondents, regardless from which department, did not differ very much. However, certain job functions and personalities have been empirically proven to be different between functional departments. These results can become a guideline in the formulation of a future teleworking program. The management must ensure that employees are willing accept this new work mode. Apart from understanding the needs of the employees and the requirements of the job, the management must also analyse the firm's existing technological abilities and foresee future capital investment in teleworking. The success of a teleworking program equally depends on adequate and reliable technological infrastructure.